Avaliação do perfil químico, variações sazonais e estudo de controle de qualidade de espécies do gênero Monteverdia: Monteverdia obtusifolia (Mart) Biral e Monteverdia rigida (Mart) Biral - Araújo, Diego Igor Alves Fernandes de (2021)
Natural products present themselves as a rich source of substances for the development of new medicines, however, maintaining the quality of materials of plant origin presents problems related to the insufficiency of phytochemical data and specifications. The species Monteverdia obtusifolia Mart and Monteverdia rigida Mart are popularly known as “good name” and are used in folk medicine to treat gastritis and ulcers. Phytochemical studies have reported the presence of triterpenes, flavonoids and alkaloids in their chemical compositions. However, there are no quality control studies reported for the species. Thus, the objectives of this work were to carry out the quality control of plant materials, to validate analytical methodologies for the quantification of phenolic compounds in the ethanolic extracts obtained from the species and to verify the seasonal variations in the chemical composition of M. obtusifolia. Optimized parameters for extracting the markers, determining water in drugs, total and sulfated ashes, granulometric analysis of powders, limit testing of heavy metals, apparent density of solids and microbiological contamination were evaluated according to the methodologies of the Brazilian Pharmacopoeia 6th edition. The quantifications of flavonoids (TF) and total phenolic compounds (TPC) were performed by a validated spectrophotometric method, using quercetin and gallic acid as standards. The chemical compositions of the species were evaluated by dereplication of the extracts obtained and seasonal variations were verified using multivariate analyzes (PCA / HCA). The crude ethanol extracts obtained from the leaves of M. obtusifolia (EEBMO) and leaves (F), stem (C), root bark (CR) and roots (R) of M. rigida were produced with particles containing > 600 μm and <1200 μm in size and subjected to agitation, after optimization of the extraction conditions. The analytical method by (HPLC-PDA) for the markers (-)-Epigallocatechin (EPG), (+)-Catechin (CAT) and (-)-Epicatechin (EPI) was validated and presented compliance for all parameters established by the RDC 166/2017. It was possible to verify that the species presented richness of phenolic compounds, flavonoids and flavan-3-ols, with a higher prevalence for the months of October and November in the species M. obtusifolia, as well as in the extract from the leaves of M. rigida. The quenching used in M. obtusifolia did not promote significant statistical differences (p <0.05) for the markers (EPG, CAT and EPI) when drying in an oven. The analysis of (PCA) confirmed the positive correlation between solar radiation and temperature, in addition to the negative effect of rainfall and humidity on the production of the evaluated markers (EPG, CAT, EPI, TF and TPC). The grouping performed by the HCA tool confirmed the data observed in the PCA with the collection of similar samples. Dereplication enabled the putative characterization of 25 phenolics in (EEBMO) with 21 unpublished reports in the species M. obtusifolia and 28 compounds in M. rigida, of which 27 were mentioned for the first time in the species. The present study made it possible to establish methodologies, parameters and specifications that are most appropriate for the evaluation of plant materials of the analyzed species of the genus Monteverdia.